They Went Out from Us : the Identity of the Opponents in First John. - Streett, Daniel R. (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche ;, 2011)
Most interpreters of 1, 2, 3 John believe that the author's opponents (called "antichrists", "deceivers", and "false prophets") advocated gnostic or progressive doctrines that denied or downplayed the humanity of Jesus Christ and the importance of ethical behaviour, and eventually split the Johannine community. Against this consensus, Streett argues that the opponents are former Jewish-Christians who have left the community to return to the synagogue after renouncing their belief that Jesus is the Jewish Messiah.